The peak frequency source of Saturn's kilometric radiation - Lamy, L.; Prangé, P.; Morooka, M.; Kurth, W. S.; Taubenschuss, U. (My University, 2023)
In 2016-2017, the Cassini spacecraft explored the source regions of Saturn0s Kilometric Radiation (SKR) within the kronian polar magnetosphere before ultimately plunging into the upper atmosphere of the planet. This powerful, non-thermal auroral radio emission analog to the Auroral Kilometric Radiation (AKR) at Earth, is radiated via the Cyclotron Maser Instability (CMI) by mildly relativistic electrons at frequencies close to the local electron gyrofrequency. The typical SKR spectrum ranges from a few kHz to ~1 MHz and thus corresponds to radiosources hosted along high latitude magnetic flux tubes from above the ionosphere up to a few kronian radii (RS). During the F-ring orbital sequence, from Nov. 2016 to April 2017, Cassini probed the outer part of both northern and southern auroral regions, ranging in altitude from ~2.5 to ~4 RS above the atmosphere, and crossed several SKR low frequency (LF) sources (~ 10 - 30 kHz). A survey showed that the SKR LF sources strongly vary with time and local time, with the lowest frequencies being reached on the dawn sector. They were additionally colocated with the UV auroral oval and controlled by local time-variable magnetospheric electron densities, with importants consequences on the use of SKR low frequency extensions as a proxy of magnetospheric dynamics. Along the final 22 proximal orbits, from April to 15th Sept. 2017, Cassini explored auroral altitudes below 2.5 RS and crossed numerous deeper SKR sources at frequencies close to, or within, the emission peak frequency (~ 80 - 200 kHz). Here, we present a first survey of these proximal orbits, taking advantage of observations of Saturn0s UV aurorae by the Hubble Space Telescope coordinated with Cassini in situ radio and magnetic measurements. Understanding how the CMI operates in the widely different environments of solar system magnetospheres is important for the ongoing search of radio emissions from exoplanets, ultracool dwarves and active stars.
Planetary, Solar and Heliospheric Radio Emissions IX
PUBLISHED